The DYNAMICS OF SHIRKAH AND MUDHARABAH: SOCIOLOGICAL AND ANTHROPOLOGICAL ANALYSIS IN THE CONTEXT OF MODERN SOCIETY - Heryana, Sandi; Arifin, Tajul; Jubaedah, Dedah (ANAYASA : Journal of Legal Studies, 2025)
This study aims to analyze the dynamics of syirkah and mudharabah from a sociological and anthropological perspective in the context of modern society. As two forms of business cooperation in Islamic economics, syirkah and mudharabah face challenges and changes due to social, economic, and cultural developments. This research employs a descriptive method by analyzing secondary data from relevant literature and documents to reveal how social structures and cultural norms influence the practice of syirkah and mudharabah. The findings suggest that changes in social relationships, cultural norms, and the global economic system significantly shape the adaptation of these concepts in the modern era. These insights are expected to contribute to the development of Sharia-based economic collaborations that are more responsive to modern social and cultural dynamics.